Lawfulness of a randomised trial of the new community treatment order regime for England and Wales. - Dawson, J; Burns, T; Rugkåsa, J (2011)
This article debates and defends the lawfulness of a randomised controlled trial of compulsory outpatient treatment under the mental health legislation for England and Wales. The trial is designed to compare the outcomes for patients of their treatment under the new Community Treatment Order (CTO) regime with their treatment under the older leave scheme - the two main forms of compulsory care in the community now authorised by the revised Mental Health Act 1983. The methods for the trial involve the random allocation of some patients between the two schemes, when they are considered by their Responsible Clinicians to be eligible for some form of compulsory outpatient care. The main question we consider is the lawfulness of that aspect of the methods. Can a carefully selected group of patients be allocated at random between the two regimes to permit an evaluation to proceed? Or would that involve some departure from the decision-making criteria specified by law? We argue that a group of patients can be identified who meet - simultaneously - the tests for treatment under both the CTO and the leave schemes. Those patients could then be allocated lawfully to treatment under either scheme. This opens the door, we argue, to their random allocation between the two schemes for the purposes of the research. In reaching this conclusion, we explain the methods and aims of the trial and closely compare the respective features of the leave and CTO regimes.